2009
DOI: 10.1097/opx.0b013e3181993f42
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Errors and Amblyopia in Children Entering School: Shahrood, Iran

Abstract: A considerable proportion of 6-year-old children have strabismus and/or significant, potentially amblyogenic refractive errors. The relatively high rate of hyperopia and astigmatism in the studied population needs more attention. The results of the study emphasize the need for adequate diagnostic and therapeutic eye care services for preschool children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 16 publications
2
67
1
1
Order By: Relevance
“…23 Strabismus was found in 2.37% of children in our study compared to 2.5% in a Turkish study, 24 and 1.2% in an Iranian study. 25 Children already known to have strabismus as well as those presenting with manifest squint during our examination were recorded. None of the children were occluded in search for intermittent exotropia, hence, we believe the reported rate of strabismus in the current study was underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…23 Strabismus was found in 2.37% of children in our study compared to 2.5% in a Turkish study, 24 and 1.2% in an Iranian study. 25 Children already known to have strabismus as well as those presenting with manifest squint during our examination were recorded. None of the children were occluded in search for intermittent exotropia, hence, we believe the reported rate of strabismus in the current study was underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Myopia occurs at a similar rate (15% to 22.2%) in adult populations [29][30][31][32][33][34] . Other ocular diseases occur at a lower rate in the general population including amblyopia (0.8-3%) 30,[35][36][37] and strabismus (0.8-3.3%) 30,35,36,38 . Clinically significant visual acuity deficit is therefore an unlikely consequence of transient subfoveal fluid just after birth.…”
Section: Discussionmentioning
confidence: 99%
“…Those studies revealed a relatively higher morbidity of myopia in some East Asian countries. The difference was found to be greater if preschool and school age children were evaluated (table 2) [13,14,15,16,17,18,19,20,21,22,23,24]. Studies on schoolchildren in Hong Kong and medical students in Singapore even revealed extremely high prevalences of 82% and 90% [25,26].…”
Section: Introductionmentioning
confidence: 99%